An investigation of risk factors for renal cell carcinoma by histologic subtype in two case‐control studies. Issue 11 (15th January 2013) - Purdue, Mark P.; Moore, Lee E.; Merino, Maria J.; Boffetta, Paolo; Colt, Joanne S.; Schwartz, Kendra L.; Bencko, Vladimir; Davis, Faith G.; Graubard, Barry I.; Janout, Vladimir; Ruterbusch, Julie J.; Beebe‐Dimmer, Jennifer; et al.
Abstract To investigate whether renal cell carcinoma (RCC) histologic subtypes possess different etiologies, we conducted analyses of established RCC risk factors by subtype (clear cell, papillary and chromophobe) in two case‐control studies conducted in the United States (1, 217 cases, 1, 235 controls) and Europe (1, 097 cases, 1, 476 controls). Histology was ascertained for 706 U.S. cases (58% of total) and 917 European cases (84%) through a central slide review conducted by a single pathologist. For the remaining cases, histology was abstracted from the original diagnostic pathology report. Case‐only analyses were performed to compute odds ratios (ORs) and 95% confidence intervals (CI) summarizing subtype differences by age, sex and race. Case‐control analyses were performed to compute subtype‐specific ORs for other risk factors using polytomous regression. In case‐only analyses, papillary cases (N = 237) were older (OR = 1.2, 95% CI = 1.1–1.4 per 10‐year increase), less likely to be female (OR = 0.5, 95% CI = 0.4–0.8) and more likely to be black (OR = 2.6, 95% CI = 1.8–3.9) as compared to clear cell cases (N = 1, 524). In case‐control analyses, BMI was associated with clear cell (OR = 1.2, 95% CI = 1.1–1.3 per 5 kg/m2 increase) and chromophobe RCC (N = 80; OR = 1.2, 95% CI = 1.1–1.4), but not papillary RCC (OR = 1.1, 95% CI = 1.0–1.2; test versus clear cell, p = 0.006). No subtype differences were observed for associations with smoking, hypertension or family history of kidney cancer. Our findings support the existence of distinct age, sex and racial distributions for RCC subtypes, and suggest that the obesity‐RCC association differs by histology.